ESTIMATION OF GENETIC PARAMETERS AND COMBINING ABILITY FOR CHARACTERS RELATED TO POTATO PROPAGATION BY TRUE POTATO SEED - Kumar, Raj; Kang, G. S.; Pandey, S. K. (Potato Journal, 2013)
One hundred fourteen progenies from line tester (19 S26) design were studied for 10 characters in seedling and seedling-tuber crops. Specific combining ability (SCA) variance was predominant in expression of various traits than the general combining ability (GCA) variance except for tuber shape, which had almost equal variances. Genotypes JX 90, CP 3125 and JN 1197 were found superior in both crops based on their GCA for all the traits. Kufri Bahar S2JN 1197, JF 4841 S2CP 3125, JX 90 S2JN 1197, CP 2161 S2JN 1197, JX 90 S2CP 3125 and JV 67 S2JEX/A 592 were superior crosses for developing high yielding and uniform true seed populations.